As Corporealidades Queer de António Variações e de José Pérez Ocaña - Pires Pepe, Paulo (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
hroughout time, secular institutions have persisted in prevailing our bodies and legislating against gender, sexual acts, sexualities considered divergent from social conventions. Performances have been examined in comparable ways by religious institutions. Taking into account particular religious and political constraints, I will in this paper look into two particular figures of the Portuguese and Spanish musical and artistic scenes: António Variações, a Portuguese gay singer that gained attention for his eccentric look and for his musical style which combined several styles of music like fado, pop, rock; and José Pérez Ocaña, a gay performer and drag queen that stood against Franco’s regime. Thus, in this article, I will comparatively draw attention to the ways that António Variações and José Pérez Ocaña bodies and performances subverted these dictatorships ideologies and celebrated a queer identity, during the Portuguese and Spanish transition from a dictatorship to democracy.